Identification of Molecular Targets and Potential Mechanisms of Yinchen Wuling San Against Head and Neck Squamous Cell Carcinoma by Network Pharmacology and Molecular Docking - Zhang, Biyu; Liu, Genyan; Wang, Xin; Hu, Xuelei (Frontiers in Genetics, 2022)
Head and neck squamous cell carcinoma (HNSCC) represent one of the most malignant and heterogeneous tumors and the patients have low 5-year survival. Traditional Chinese medicine (TCM) has been demonstrated as effective complementary and/or alternative therapies for advanced malignancies including HNSCC. It has been noted that several herbs that used for preparing Yinchen Wuling San (YWLS) have anti-tumor activities, whereas their mechanisms of action remain elusive. In this study, network pharmacology and molecular docking studies were employed to explore the underlying mechanisms of action of YWLS against HNSCC. The 58 active ingredients from 6 herbs used for YWLS and their 506 potential targets were screened from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and SwissTargetPrediction database. A total of 2,173 targets that associated with HNSCC were mainly identified from the DisGeNET and GeneCards databases. Active components-targets-disease network was constructed in the Cytoscape. Top 20 hub targets, such as AKT1, EGFR, TNF, ESR1, SRC, HSP90AA1, MAPK3, ERBB2, and CCND1, were identified by degree in the protein-protein interaction (PPI) network. Gene functional enrichment analysis showed that PI3K-AKT, MAPK, Ras, TNF, and EGFR were the main signaling pathways of YWLS in treating HNSCC. There were 48 intersected targets such as EGFR, AKT1 and TNF that were associated with patients’ outcome by the univariate Cox analysis, and most of them were increased expression in the tumor as compared to normal tissues. The area under curves of receiver operating characteristic indicated their diagnostic potential. Inhibition of these survival-related targets and/or combination with EGFR or AKT inhibitors were promising therapeutic options in HNSCC. The partial active components of YWLS exhibited good binding with the hub targets, and ADME analysis further evaluated the drug-likeness of the active components. These compounds and targets identified in this study might provide novel treatment strategies for HNSCC patients, and the subsequent work is essential to verify the underlying mechanisms of YWLS against HNSCC.